Conflicts between bikes and trucks in urban areas—A survey of Norwegian cyclists. Issue 1 (March 2018) - Pokorny, Petr; Pritchard, Ray; Pitera, Kelly
Highlights: Unique study of truck-bicycle conflicts in urban areas is introduced. Cyclists report significant numbers of conflicts with trucks. Conflicts connected with overtaking manoeuvres being the most frequent. Variable city affects the conflict type, proposing the impact of local conditions. Abstract: Several challenges accompany the current growth of bike and truck volumes in urban areas, with traffic safety being one of the most critical concerns. Bike-truck accidents present a direct measure of the safety; however, these are rare events. Furthermore, accident records are subject to several shortcomings. Thus, safety studies should not rely solely on accident analysis, and conducting the additional methods is advisable (e.g. surveys or conflict analysis). This paper discusses the results of a retrospective survey of Norwegian utilitarian cyclists, which collected data about their involvement in conflicts with trucks in urban areas. An online questionnaire was disseminated within major cities in Norway, and 631 valid responses were analysed. The results revealed large numbers of conflicts experienced by cyclists, with the most frequent types of conflicts being (1) truck overtaking bicyclist and (2) right-turning truck vs. straight-riding bicyclist and. Visibility issues were frequently mentioned as the important risk factors. Almost all cyclists blamed truck drivers as the party responsible for the conflict. The distribution of conflict categories differed between major Norwegian cities, which corresponds with the findings of a previous accident analysis. Insights developed are useful to local policy makers both in Norway and abroad, when considering how to plan for increasing numbers of cyclists and trucks in urban areas.